(untitled) (Research, Society and Development, 2020)
Currently, the search for a harmonic and beautiful smile, makes darkened teeth of great discomfort for patients, leading to the search for an aesthetic treatment to change the color and shape of the teeth. Dentistry has several aesthetic restorative techniques, including ceramic laminates, which are a minimally invasive option and have properties such as biocompatibility, color stability, longevity and resistance, that is, they present biomimicry with enamel. Thus, the purpose of this work is to report a clinical case in which the patient initially had a darkened anterior tooth due to endodontic treatment, where an external tooth whitening was performed, a wear of approximately 0,3mm, and the cementation of the ceramic veneers. The use of ceramic laminates in dentistry brings satisfactory results when combined with durability, minimal wear, aesthetics and resistance. With the mastery of the professional, proper restoration technique, correct case planning, and careful execution of clinical steps, a positive result is obtained. Returning the patient’s naturalness, harmony and self-esteem.